Non-pharmacological interventions in primary care to improve the quality of life of older patients with palliative care needs: a systematic review protocol - Carlos Martins; Barbara Gomes; Matilde Monteiro-Soares; Filipe Prazeres; Carlos Seiça Cardoso; Joana Rita Matos (BMJ Open)
Introduction In the last decades, the number of older people living with chronic diseases has rapidly increased. The prevalence of palliative care needs in this population can reach 17%, making the general practitioner a cornerstone in the identification and first medical intervention delivery. Therefore, knowing the primary care interventions that effectively improve the quality of life of these patients can play an important role in the delivery of healthcare.Methods and analysis We will systematically review randomised controlled trials evaluating the effect of non-pharmacologic primary care interventions on the quality of life of older patients (≥65 years) with palliative care needs. PsycINFO, EMBASE, MEDLINE, Cochrane and CINAHL will be searched until December 2021. Screening, data extraction and quality evaluation (using the Cochrane RoB 2.0 tool) will be done by independently by two reviewers, with disagreements solved by a third reviewer. We will conduct meta-analysis if appropriate. In case of high heterogeneity, findings will be analysed by subgroup according to intervention type, main disease/symptoms and care context. Evidence will be graded using the Grading of Recommendations Assessment, Development and Evaluation approach. We will perform a sensitivity analysis based on study quality. Publication bias will be assessed using funnel plots.Ethics and dissemination Formal ethical approval is not required as primary data will not be collected. The results will be disseminated through a peer-reviewed publication, conference presentation and the press.PROSPERO registration number CRD42020154216.